Treatment of ventilator-associated pneumonia due to carbapenem-resistant Gram-negative bacteria with novel agents: a contemporary, multidisciplinary ESGCIP perspective. Issue 7 (3rd July 2022) - Giacobbe, Daniele Roberto; Roberts, Jason A.; Abdul-Aziz, Mohd H.; de Montmollin, Etienne; Timsit, Jean-François; Bassetti, Matteo
ABSTRACT: Introduction: In the past 15 years, treatment of ventilator-associated pneumonia (VAP) caused by carbapenem-resistant Gram-negative bacteria (CR-GNB) has represented an intricate challenge for clinicians. Areas covered: In this perspective article, we discuss the available clinical data about novel agents for the treatment of CR-GNB VAP, together with general pharmacokinetic/pharmacodynamic principles for the treatment of VAP, in the attempt to provide some suggestions for optimizing antimicrobial therapy of CR-GNB VAP in the daily clinical practice. Expert opinion: Recently, novel β-lactams and β-lactam/β-lactamase inhibitor combinations have become available that have shown potent in vitro activity against CR-GNB and have attracted much interest as novel, less toxic, and possibly more efficacious options for the treatment of CR-GNB VAP compared with previous standard of care. Besides randomized controlled trials, a good solution to enrich our knowledge on how to use these novel agents at best in the near future, while at the same time remaining adherent to current evidence-based guidelines, is to improve our collaboration to conduct larger multinational observational studies to collect sufficiently large populations treated in real life with those novel agents for which guidelines currently do not provide a recommendation (in favor or against) for certain causative organisms.